Foreign policy intervention, involvement, or isolation? - Wolf, Alvin 1935- (Inquiry into crucial American problems, 1977)
Presents divergent viewpoints regarding the United States' past, present, and future political, economic, humanitarian, and diplomatic involvements with other nations.